Представьте в виде многочлена 1.4(m-n)(m+n) 2.0.5(2x-y)(2x+y) 3.3a(a+b)(a-b) Упростить выражение 5(b-c)(b+c)-5(b^2-a^2)
Представьте в виде многочлена
1.4(m-n)(m+n)
2.0.5(2x-y)(2x+y)
3.3a(a+b)(a-b)
Упростить выражение
5(b-c)(b+c)-5(b^2-a^2)
Ответ(ы) на вопрос:
[latex]1) \ \ 4(m-n)(m + n) = 4(m^2 + mn - nm -n^2) = 4m^2 - 4n^2\\\\ 2) \ \ 0.5(2x - y)(2x + y) = 0.5(4x^2 + 2xy - y2x - y^2) = 2x^2 - 0.5y^2\\\\ 3) \ \ 3a(a + b)(a - b) = 3a(a^2 - ab + ba - b^2) = 3a^3 - 3ab^2[/latex]
[latex]5(b - c)(b + c) - 5(b^2 - a^2) = 5(b^2 - c^2) - 5(b^2 - a^2) =\\ = 5b^2 - 5c^2 - 5b^2 + 5a^2 = 5a^2 - 5c^2 = 5(a^2 - c^2) = 5(a + c)(a - c)[/latex]
Не нашли ответ?
Похожие вопросы